The effect of external fixator on bone metabolism in patients with open fracture of extremities: External fixator promotes bone metabolism - Shi, Yu; Niu, Feng; Liu, Zhong; Teng, Yunsheng; Jiao, Jian; Xu, Pingan; Ma, Ning; Gao, Baoquan; Liu, Beibei; Gao, Fang (Cellular and Molecular Biology, 2024)
This experiment aimed to explore the influence mechanism of external fixator on open fracture. A total of 128 patients with open tibiofibular fractures were included in this study. The patients were randomly divided into external fixator group (n=64) and control group (n=64) according to the order of admission. Double-blind controlled observation was used. The levels of osteocalcin (BGP), β-CTX, P1 NP, BALP, including haptoglobin (Hp), ceruloplasmin (CER), serum adrenocorticotropic hormone (ACTH), cortisol (COR), C-reactive protein (CRP), white blood cell (WBC) and interleukin-6 (IL-6) were recorded in different groups. The postoperative VAS score and quality of life were recorded. Log-rank was used to analyze the difference in postoperative adverse reaction rates among different groups. External fixation stent treatment increased BGP, PINP, and BALP expression and decreased β-CTX, Hp, CER, ACTH, COR, CRP, WBC, and IL-6 levels. Patients in the external fixation stent group had significantly lower VAS score quality of life scores and incidence of adverse events than the control group. External fixation stents protect open fracture patients by promoting bone metabolism.